The effect of cannabinoid type Ⅱ receptor on the excitability of substantia nigra dopaminergic neurons - Zhao, Sha; Liu, Shunfeng; Gong, Yongxin; Ma, Zegang (Frontiers in Pharmacology, 2025)
The biological effects of cannabinoids are mainly mediated by two members of the G-protein-coupled-receptor family: cannabinoid type 1 receptor (CB1R) and cannabinoid type 2 receptor (CB2R). Unlike CB1R, CB2R is considered a “peripheral” cannabinoid receptor. However, recent studies have found that CB2R is widely expressed in the central nervous system and is involved in dopamine related behavioral regulation, including dietary behavior, weight regulation, anxiety, and schizophrenia like behavior. Our previous laboratory research demonstrated that activating CB2R on dopaminergic neurons in the ventral tegmental area can regulate addictive behavior in animals by inhibiting neuronal excitability. However, it is currently unclear whether CB2R on dopaminergic neurons in the substantia nigra compacta (SNc) has similar therapeutic potential. Brain patch clamp results have shown that the CB2R agonist JWH133 significantly inhibits the discharge of SNc dopamine neurons in a concentration dependent manner. The pharmacological blocker AM630 of CB2R can reverse this inhibitory effect, indicating that the expression of CB2R in SNc dopaminergic neurons is functional. After treatment with JWH133, the number of induced action potentials decreased, and the peak potential interval time, action potential start time, and potential amplitude after hyperpolarization amplitude all increased. In addition, synaptic current results showed that JWH133 can significantly reduce the frequency of miniature excitatory postsynaptic currents, indicating that activating CB2R to some extent inhibits the release of presynaptic glutamate and indirectly excites postsynaptic neurons.